A configurable architecture for running hybrid convolutional neural networks in low-density FPGAs - Véstias, Mário (2021)
Convolutional neural networks have become the state of the art of machine learning for a vast set of applications, especially for image classification and object detection. There are several advantages to running inference on these models at the edge, including real-time performance and data privacy. The high computing and memory requirements of convolutional neural networks have been major obstacles to the broader deployment of CNNs on edge devices. Data quantization is an optimization method that reduces the number of bits used to represent weights and activations of a network model, minimizing storage requirements and computing complexity. Quantization can be applied at the layer level, by using different bit widths in different layers: this is called hybrid quantization. This article proposes a new efficient and configurable architecture for running CNNs with hybrid quantization in low-density Field-Programmable Gate Arrays (FPGAs) targeting edge devices. The architecture has been implemented on the Xilinx ZYNQ7020/45 devices and is running the AlexNet and VGG16 networks. Running AlexNet, the architecture has a throughput up to 508 images per second on the ZYNQ7020 device, and 1639 images per second on the ZYNQ7045 device. Considering VGG16, the architecture delivers up to 43 images per second on the ZYNQ7020 device, and 81 images per second on the ZYNQ7045 device. The proposed hybrid architecture achieves up to 13.7 x improvement in performance compared to state-of-the-art solutions, with small accuracy degradation.